Formation of a Ge-rich Si1−xGex (x > 0.9) fin epitaxial layer condensed by dry oxidation. (29th September 2017) - Jang, Hyunchul; Kim, Byongju; Koo, Sangmo; Ko, Dae-Hong
Abstract: We have selectively grown an epitaxial Si0.35 Ge0.65 fin layer in a 65 nm oxide trench pattern array and formed a Ge-rich Si1− x Ge x ( x > 0.9) fin layer with condensed Ge using dry oxidation. During oxidation of the SiGe fin structure, we found that the compressive strain of the condensed SiGe layer was increased by about 1.3% while Ge was efficiently condensed due to a two-dimensional oxidation reaction. In this paper, we discussed in detail the diffusion during the two-dimensional condensation reaction as well as the asymmetric biaxial strain of the SiGe fin before and after oxidation using a reciprocal space mapping measurement. The application of dry oxidation on selectively grown SiGe fin layer can be an effective method for increasing hole mobility of SiGe fin with increased Ge content and self-induced compressive strain.